Seeing Oneself Seeing: A Conversation with Lucy Raven. - JOSELIT, DAVID (October)
An interview with film producer Lucy Raven is presented. When asked about how he was drawn to animism, he mention that relation between two types of labor as one of analogy. He comment on the making of the films that connects more to the history of animation than to the history of live-action film. He also mention about the changes he made with each work. His activity of exploring the relationship between images of labor and production. Interest of Raven in animation and shooting multiple frames of individual drawings with the rhythmic norms of standard film or video image.